Decreased basal chloride secretion and altered cystic fibrosis transmembrane conductance regulatory protein, Villin, GLUT5 protein expression in jejunum from leptin-deficient mice - Leung L (Dove Medical Press, 2014)
Lana Leung, Jonathan Kang, Esa Rayyan, Ashesh Bhakta, Brennan Barrett, David Larsen, Ryan Jelinek, Justin Willey, Scott Cochran, Tom L Broderick, Layla Al-NakkashDepartment of Physiology, Arizona College of Osteopathic Medicine, Midwestern University, Glendale, AZ, USAAbstract: Patients with diabetes and obesity are at increased risk of developing disturbances in intestinal function. In this study, we characterized jejunal function in the clinically relevant leptin-deficient ob/ob mouse, a model of diabetes and obesity. We measured transepithelial short circuit current (Isc), across freshly isolated segments of jejunum from 12-week-old ob/ob and lean C57BL/6J (female and male) mice. The basal Isc was significantly decreased (~30%) in the ob/ob mice (66.5±5.7 µA/cm2 [n=20]) (P< 0.05) compared with their lean counterparts (95.1±9.1 µA/cm2 [n=19]). Inhibition with clotrimazole (100 µM, applied bilaterally) was significantly reduced in the ob/ob mice (−7.92%±3.67% [n=15]) (P<0.05) compared with the lean mice (10.44%±7.92% [n=15]), indicating a decreased contribution of Ca2+-activated K+ (KCa) channels in the ob/ob mice. Inhibition with ouabain (100 µM, applied serosally) was significantly reduced in the ob/ob mice (1.40%±3.61%, n=13) (P< 0.05) versus the lean mice (18.93%±3.76% [n=18]), suggesting a potential defect in the Na+/K+-adenosine triphosphate (ATP)ase pump with leptin-deficiency. Expression of cystic fibrosis transmembrane conductance regulatory protein (CFTR) (normalized to glyceraldehyde-3-phosphate dehydrogenase [GAPDH]) was significantly decreased ~twofold (P<0.05) in the ob/ob mice compared with the leans, whilst crypt depth was unchanged. Villi length was significantly increased by ~25% (P<0.05) in the ob/ob mice compared with the leans and was associated with an increase in Villin and GLUT5 expression. GLUT2 and SGLT-1 expression were both unchanged. Our data suggests that reduced basal jejunal Isc in ob/ob mice is likely a consequence of reduced CFTR expression and decreased activity of the basolateral KCa channel and Na+/K+-ATPase. Understanding intestinal dysfunctions in ob/ob jejunum may allow for the development of novel drug targets to treat obesity and diabetes.Keywords: intestinal secretion, transport, ob/ob, obese, diabetes, small intestine